Therapy at 30 days of life predicts lung function at 6 to 12 months in infants with congenital diaphragmatic hernia. Issue 6 (19th March 2020) - Chotzoglou, Etze; Hedrick, Holly L.; Herkert, Lisa M.; Goldshore, Matthew A.; Rintoul, Natalie E.; Panitch, Howard B.
Abstract: Introduction: Congenital diaphragmatic hernia (CDH) is associated with variable degrees of lung hypoplasia. Pulmonary support at 30 days postnatal age was found to be the strongest predictor of inpatient mortality and morbidity among CDH infants and was also associated with higher pulmonary morbidity at 1 and 5 years. It is not known, however, if there is a relationship between the need for medical therapy at 30 days of life and subsequent abnormalities in lung function as reflected in infant pulmonary function test (iPFT) measurements. Objective: We hypothesized that CDH infants who require more intensive therapy at 30 days would have more abnormal iPFT values at the time of their first infant pulmonary function study, reflecting the more severe spectrum of lung hypoplasia. Methods: A single‐institution chart review of all CDH survivors who were enrolled in a Pulmonary Hypoplasia Program (PHP) through July 2019, and treated from 2002 to 2019 was performed. All infants were divided into groups based on their need for noninvasive (supplemental oxygen, high flow therapy, noninvasive mechanical ventilation) or invasive (mechanical ventilation, extracorporeal membrane oxygenation) respiratory assistance, bronchodilators, diuretic use, and pulmonary hypertension (PH) therapy (inhaled and/or systemic drugs) at 30 days. Descriptive and statistical analyses were performed between groups comparing subsequent lung function measurements. Results: A total of 382 infants (median gestational age [GA] 38.4 [interquartile range (IQR) = 37.1‐39] weeks, 41.8% female, 70.9% Caucasian) with CDH were enrolled in the PHP through July 2019, and 118 infants underwent iPFT. The median age of the first iPFT was 6.6 (IQR = 5.3‐11.7) months. Those requiring any pulmonary support at 30 days had a higher functional residual capacity (FRC) ( z ) ( P = .03), residual volume (RV) ( z ) ( P = .008), ratio of RV to total lung capacity (RV/TLC) ( z ) ( P = .0001), and ratio of FRC to TLC (FRC/TLC) ( z ) ( P = .001); a lower forced expiratory volume at 0.5 seconds (FEV0.5) ( z ) ( P = .03) and a lower respiratory system compliance (Crs) ( P = .01) than those who did not require any support. Similarly, those requiring diuretics and/or PH therapy at 30 days had higher fractional lung volumes, lower forced expiratory flows and Crs than infants who did not require such support ( P < .05). Conclusions: Infants requiring any pulmonary support, diuretics and/or PH therapy at 30 postnatal days have lower forced expiratory flows and higher fractional lung volumes, suggesting a greater degree of lung hypoplasia. Our study suggests that the continued need for PH, diuretic or pulmonary support therapy at 30 days can be used as additional risk‐stratification measurements for evaluation of infants with CDH.